Analisis Buku Al-Arabiyyah Bayna Yadayyk Jilid 1 Sebagai Pembelajaran Bahasa Arab Pemula Non Arab - M Hussein Wijaya; Ahmad Iqbal; Fahrul Ghazi; Erni Zuliana (STKIP Subang, 2025)
This study examines the suitability of Al-‘Arabiyyah Bayna Yadayk Book I as instructional material for beginner non-Arab learners in Indonesia, responding to the increasing need for standardized and effective Arabic learning resources. The research aims to analyze the extent to which the book aligns with Karin C. Ryding’s principles of Arabic as a foreign language instruction, including the integration of language skills, phonological reinforcement, simplified authentic input, communicative practice, cultural context, repetition-based learning, and multimedia support. Using a descriptive qualitative approach through library research, the study employs content analysis to explore the structure, progression, and pedagogical orientation of the book. The findings show that Al-‘Arabiyyah Bayna Yadayk Book I is systematically designed with graded materials covering vocabulary, dialogues, phonological training, reading and writing tasks, and culturally relevant themes. The book effectively incorporates audio support, visual context, and repetitive communicative exercises, demonstrating strong alignment with Ryding’s theoretical framework. Overall, the book provides comprehensive, structured, and contextually meaningful content, making it suitable for beginner non-Arab learners, although further adaptation to Indonesian learning contexts and enhanced digital integration may improve its effectiveness.